NATURE OF AL-SI ANTIORDERING IN A TWO-PHASE FELDSPAR FROM PEKTUSAN VOLCANO, PRIMORIE - Oganov A.R.; Oganova N.I.; Urusov V.S. (My University, 2001)
The phenomenon of antiordering, i.e., preferred Al occupation of the T-2o position of the albite structure, was observed in a two-phase feldspar from Pektusan Volcano, Primorie. This paper reports the results of the computer modeling of this phenomenon. Calculations were carried out in an ionic approximation and confirm that, under ordinary conditions, the most preferable is normal Al ordering in the T-1o position. However, if lattice parameters are fixed at the experimental values obtained for the albite from Pektusan Volcano, the antiordered structure becomes energetically preferable. Based on theoretical calculations and crystal structure analysis, it was stated that antiordering can occur as a consequence of a peculiar deformation of the structure (compression along the c axis and/or extension along the b axis). Such a deformation (extension along b) was detected in the albite from Pektusan Volcano at coherent boundaries ((6) over bar 01) with potassium feldspar in the spinodal exsolution structures. The lamellae of coexisting potassium feldspar experience an opposite deformation and show no change in the type of ordering. The mechanism that we propose for the explanation of the antiordering phenomenon can be described in general terms as forced equilibrium caused by elastic strain at inter-growth boundaries. The calculations show also that the antiordered structure might be thermodynamically more stable at pressures of the order of tens of kilobars, corresponding to deep lithosphere. The predicted phase transition from a normally ordered to an antiordered structure is isosymmetric. Calculations based on the ionic model and preliminary results obtained by the Hartree-Fock method suggest a correlation between the type of Al-Si ordering and the position of Na atoms in the structure.